Pengaruh Biaya Pencegahan, Biaya Penilaian, Dan Biaya Kegagalan Internal Terhadap Produk Rusak - Wahid Suyoto, Agus; Azlina (BULLET : Jurnal Multidisiplin Ilmu, 2024)
One way to maintain consistent quality and reduce losses caused by defective products is through preventive costs, assessment costs, and internal failure costs. This research aims to: (1) Determine the combined impact of preventive costs, assessment costs, and internal failure costs. (2) Identify which of these costs—preventive, assessment, or internal failure has a greater influence on defective products. The research method employed is quantitative descriptive. Sample selection follows the Purposive Sampling method, using quality cost reports from the ASQIRO packaged drinking water company for the years 2020–2023. Hypothesis testing is conducted using (1) F-test, (2) coefficient of determination test, (3) t-test, and SE/SR calculations. Based on the research results, there is a significant influence of preventive costs, assessment costs, and internal failure costs both simultaneously (as indicated by an F-test significance value of 0.000 < 0.05) and individually (parsially) with t-test results showing significance values for preventive costs (0.000 < 0.05), assessment costs (0.030 < 0.05), and internal failure costs (0.032 < 0.05). The study also reveals that preventive costs (SE: 49.00%) have a greater impact on defective products compared to assessment costs (SE: 21.04%) and internal failure costs (SE: 3.09%).